ANALISIS GERAK PENUMPANG PADA TABRAKAN FRONTAL DENGAN MENGGUNAKAN SIMULASI KOMPUTER - Ary Subagia, I.D.G; Kade Suriadi, I.G.A (Jurnal Energi Dan Manufaktur; Vol 2, No.2 Desember 2007, 2012)
Frontal direction crash has become most serious cause in traffic accident. Based on the fact, this reaserch focused on the passenger movement in a frontal crash. The research was aimed to predict the direction of passenger movement and the benefit of using the seatbelt to decelerate the passenger movement in a frontal crash. The research was conducted by computer simulation by using Delphi 7. The inputs were vehicle velocity (80 km/h), mass of passenger (75 kg), and mass of vehicle (2000 kg). The results showed that in a frontal crash the deceleration of the passenger was smaller than that of the vehicle. The result of simulation showed that the force on passenger was 1.8352 N. If seatbelt tightness 1 N/cm2 was applied, the force on passenger decreased 468.56 N. In this case, the passenger still had relative velocity to the vehicle vrf = 1.75728 m/s and the force on passenger was 249.46 N. The seatbelt had important function to decelerate the passenger movement to the same deceleration of the vehicle during the frontal crash.
Keywords: Frontal crash, simulation, relative acceleration, passenger